Nanoencapsulation as a novel delivery approach for therapeutic applications of gla-rich protein (GRP) - Araújo, Nuna (2021)
Gla rich protein (GRP) is a vitamin K dependent protein, shown to function as an inhibitor of pathological calcification and as an anti-inflammatory agent, with potential therapeutic use for age-related diseases such as osteoarthritis (OA) [1,2]. OA is a leading cause of disability and morbidity in the older population and constitutes a major world wide challenge for our health system. Presently, there are no drugs approved that can prevent, stop, or even restrain progression of OA. GRP has been shown to be able to lower inflammation and mineralisation processes in the articular tissue. Chitosan/tripolyphosphate (TPP) nanoparticles were selected for this study due to their biocompatibility, biodegradability and capacity to overcome the problem of low solubility of GRP in physiological conditions. This study aims to produce and characterise chitosan/TPP nanoparticles as GRP-delivery vehicles and test its anti-inflammatory potential in human macrophages.